2012
DOI: 10.1152/ajpgi.00275.2011
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits interferon-γ signaling in colonic epithelial cells

Abstract: Midura-Kiela MT, Radhakrishnan VM, Larmonier CB, Laubitz D, Ghishan FK, Kiela PR. Curcumin inhibits interferon-␥ signaling in colonic epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 45 publications
(51 reference statements)
3
36
0
Order By: Relevance
“…Another study has found that the highest achieved peak serum concentration of curcumin in the peripheral blood was only 139 nM measured 4 hours after a single oral dose of 12 g curcumin 35 . Further, limited transepithelial flux and rapid metabolism in the gut epithelium are likely to impair curcumin exerting its beneficial effect locally on gut epithelium 36 . In our in vitro experiments, curcumin was delivered via DMSO, which would enhance delivery to the cell cytoplasm.…”
Section: All Authors Contributed To Conception and Design Manuscriptmentioning
confidence: 99%
“…Another study has found that the highest achieved peak serum concentration of curcumin in the peripheral blood was only 139 nM measured 4 hours after a single oral dose of 12 g curcumin 35 . Further, limited transepithelial flux and rapid metabolism in the gut epithelium are likely to impair curcumin exerting its beneficial effect locally on gut epithelium 36 . In our in vitro experiments, curcumin was delivered via DMSO, which would enhance delivery to the cell cytoplasm.…”
Section: All Authors Contributed To Conception and Design Manuscriptmentioning
confidence: 99%
“…The intestinal epithelium, an essential component of the gut innate defense mechanisms, is profoundly affected by interferon-γ, which can disrupt the epithelial barrier function, prevent epithelial cell migration and wound healing, as well as prime epithelial cells to express major histocompatibility complex class II molecules and to serve as nonprofessional antigen-presenting cells [43]. Recently, curcumin has also been shown to act as an interferon-γ-signaling inhibitor in colonocytes [43].…”
Section: Curcumin and Immune Functionmentioning
confidence: 99%
“…Recently, curcumin has also been shown to act as an interferon-γ-signaling inhibitor in colonocytes [43]. …”
Section: Curcumin and Immune Functionmentioning
confidence: 99%
“…A high-calorie diet is the one of the major factors contributing to the development of obesity [3]. Specifically, it has been reported that administration of a high fat diet (HFD) results in abnormal lipid accumulation in the liver [4] and an increase in triglyceride, total cholesterol, and low density lipoprotein (LDL) in the blood serum [5]. It is very difficult to achieve weight loss and improve its abnormality once weight exceeds the normal range.…”
Section: Introductionmentioning
confidence: 99%